Involvement and detachment in intellectual disability studies - Marcel Calvez (Scandinavian Journal of Disability Research, 2009)
Attention given to the role of researchers in qualitative methods questions the conditions of production of knowledge on the experience of persons with intellectual disabilities. The involvement of researchers has to be discussed regarding their interactions with members of a muted group labelled as having social and communicative incompetence. The article discusses the interest of first person researchers’ texts in the approach to the social experience of intellectual disability. It advocates a reasonable use of personal accounts of research to explain the conditions of production of knowledge and develop comparability between studies.